PENGARUH INSENTIF, PELATIHAN DAN KEMAMPUAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. OPTIK TUNGGAL SEMPURNA - Firla Oktafiani dan Yolanda (Fakultas Ekonomi Universitas Borobudur, 2017)
Efforts to improve the quality of human resources, especially human resources company needs to be done well, directed, and planned, so that companies can compete in a healthy manner with other companies, given the future competition between companies will be more stringent. HR that can compete with competitors or with business partners is only companies that have quality human resources. The purpose of the study was to determine the effect of incentives and work ability, on employee performance of PT. optik Tunggal Sempurna.This study used survey method using primary data obtained from questionnaire. The sample in this research is 50 employees. Samples were taken by accidentally sampling technique ie sampling technique when all members of population used as sample. Data analysis technique using Path Analysis. The results showed that the correlation coefficient obtained positive value that reflects that the incentive and work ability have a positive relationship with achievement, so the higher the ability of work and incentives, the higher the achievement of employees. From the results obtained also known coefficient of determination that reflects how big the contribution of free variables (motivation and leadership patterns) to the dependent variable (performance), ie 0.905 or 90.5%, it means incentives and work ability affect the achievement of 90.5% Of 9.5% influenced by other factors that are not in carefully. 1. There is influence of incentive and work ability influence to employee performance of PT. Optik Tunggal Sempurna simultaneously. 2. There is influence of incentive affect on employee work performance of PT. Perfect Single Optics partially. 3. There is influence of work ability influence to employee performance of PT. Optik Tunggal Sempurna partially. Keywords: incentives, training, and ability, employee achievement.